Novel Direct Downhole Enthalpy Estimation at Geothermal Well in Cubadak, West Sumatra, Indonesia - Anggoro Wisaksono (Formosa Journal of Applied Sciences, 2022)
Temperature, pressure and enthalpy data are very important and valuable, both during geothermal drilling and in well operation. Fibre optic distributed temperature sensors (DTS) that offer flexible and robust solutions for geothermal applications and temperature logging, an established method for well temperature measurement. All temperature measurement methods will be combined with reservoir enthalpy estimation using T-p-x state space correlation for H2O-NaCl geothermal brine. A geothermal brine enthalpy estimation model has been developed, based on T-p-x state space correlation using C programming language. This was able to provide estimations of pressure, mass fraction, density and enthalpy, solely based on measured temperature limited to below 300oC. The model can be applied to various geothermal fields with sodium chloride dominated waters. The study treated the mixture of geothermal brine and drilling fluid heated in the well for certain periods as a simulation of geothermal brine at the reservoir. The enthalpy monitoring graph proved useful for monitoring the enthalpy in the reservoir. The results from the model are used for early electrical power estimations of the Cubadak geothermal working area site, based on current geothermal gradient extrapolation of CBD-1 well.